(untitled) (Applied Biological Research, 2018)
Nannochloropsis salina D.J. Hibberd, a marine microalga, has aquaculture and biotechnological potential. The present study was aimed at to assess the influence of common plant growth regulators on growth and pigment composition of microalga N. salina. The addition of indole-3-acetic acid (IAA) to growth medium at lower concentration (0.1 mg L-1) slightly promoted algal growth while 2,4-dichlorophenoxy acetic acid (2,4-D) decreased the growth. Lower concentrations of auxins enhanced chlorophyll a production in N. salina while higher concentration inflicted inhibition. Addition of kinetin in medium negatively influenced the growth rate and pigment production while 6- benzylaminopurine (BAP) promoted algal growth at lower concentrations (0.1 mg L-1) but positively influenced pigment production at 2 mg L-1.